International economics - Carbaugh, Robert J., 1946- (Cincinnati, OH : South-Western College, 2000)
The international economy. Foundations of modern trade theory. International equilibrium. Trade model extensions and applications. Tariffs. Nontariff trade barriers. Trade regulations and industrial policies. Trade policies for the developing nations. Regional trading arrangements. International factor movements and multinational enterprises. The balance of payments. Foreign exchange...
Keywords: Economics; International economic relations